(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Madhumeha, one among the Vataja Pramehas need utmost consideration in the current scenario in view of the rising incidence. Madhumeha is similar to diabetes mellitus. Diabetes Mellitus is a chronic metabolic disease characterized by elevated levels of blood glucose which leads over time to serious damage to the heart, blood vessels, eyes, kidneys and nerves. The most common is Type 2 Diabetes, usually in adults, which occurs when the body becomes resistant to Insulin or doesn’t make enough Insulin. In the past 3 decades the prevalence of Type 2 Diabetes has raised dramatically in countries of all income levels. According to Ayurveda, Madhumeha is manageable with the prescribed Chikitsa in the Samhitas. It is judiciously managed with the help of Yuktikruta Ahara, Vihara and Aushadha (Darvyadi churna). In this case Nidana parivarjana has been followed and this case is being considered as Sthoola Pramehi.